PERAN TRAVEL VLOG YOUTUBE SEBAGAI ELECTRONIC WORD OF MOUTH TERHADAP REVISIT INTENTION WISATAWAN: STUDI PADA KONSUMEN LEMBANG PARK AND ZOO - Melfina Nurul Azizah; Usep Suhud; Dewi Agustin Pratama Sari (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the effect of travel vlogs as video-based electronic word of mouth (e-WOM) on destination image, attitude toward destination, and tourist satisfaction in influencing revisit intention at Lembang Park & Zoo. Data were collected through an online questionnaire distributed to respondents who have watched travel vlogs related to Lembang Park and Zoo. This study employed a quantitative method using Structural Equation Modeling (SEM) with the assistance of SPSS and AMOS for data analysis. The results show that travel vlogs have a positive and significant effect on destination image, attitude toward destination, and tourist satisfaction, and these variables also have a positive and significant effect on revisit intention. These findings indicate that travel vlogs not only function as a source of information, but also shape tourists’ perceptions, attitudes, and evaluations, which in turn encourage revisit intention. Practically, destination managers should ensure that the quality of the tourist experience is consistent with how it is represented in travel vlogs.